2015
DOI: 10.1159/000430858
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Ovarian Malignancy Algorithm (ROMA) as a Predictive Marker of Peritoneal Dissemination in Epithelial Ovarian Cancer Patients

Abstract: Background: This study aimed to determine the efficacy of the risk of ovarian malignancy algorithm (ROMA), calculated using the carbohydrate antigen 125 (CA125) and human epididymis protein 4 (HE4) levels and the menopausal status, as a predictor of peritoneal dissemination in ovarian cancer. Methods: The CA125 and HE4 levels and the ROMA were compared between ovarian cancer patients (n = 122) with or without peritoneal dissemination. The sensitivity, specificity, positive predictive value, and negative predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous reports on HE4 in the differential diagnosis of pelvic mass included mostly patients with advanced (stage III or IV) ovarian cancer [15][16][17][18]33]. For those patients, tumor markers such as HE4 are of marginal clinical value because the risk of malignancy is easily established by the presence of clinical indicators (omental caking, peritoneal deposits and ascites) alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on HE4 in the differential diagnosis of pelvic mass included mostly patients with advanced (stage III or IV) ovarian cancer [15][16][17][18]33]. For those patients, tumor markers such as HE4 are of marginal clinical value because the risk of malignancy is easily established by the presence of clinical indicators (omental caking, peritoneal deposits and ascites) alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports regarding the benefit of HE4 and ROMA, with some studies showing that HE4 and ROMA can better predict the likelihood of malignancy than CA125 [15][16][17], while others show no benefit of HE4 and ROMA [18,19]. In addition, it is important to remember that detection of HE4 has been applied in clinical centers in South China for just one and a half years.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of ovarian malignancy algorithm (ROMA) combines HE4 with CA125 measurements into an algorithm based upon menopausal status and has been recommend to classify patients with OT as either low-or high-risk (9). Some studies have reported that ROMA yields more accurate predictions of the presence of malignant OTs than either CA125 or HE4 alone (10,11) while others have reported no benefits from using either CA125 or HE4 in calculating OC risk (12). There is controversy in the literature regarding the cut-off values for HE4, CA125, and ROMA in differentiating between benign and malignant OTs (13,14).…”
Section: Introductionmentioning
confidence: 99%